Communicative Approach to Teaching a Foreign Language - Nigmatova Dilsoz Yadgarovna (Universitas Muhammadiyah Sidoarjo, 2022)
This article is dedicated to the effectiveness of the introduction of various methods and techniques based on the content for the development of students' language skills in practice. Modern methodology requires foreign language teachers to implement all language skills in one lesson. The ability to speak, listen and understand authentic material in English, as well as reading and writing skills should be taught in an integrated form; once available, it can be a difficult process for the teacher and students. But with the help of various innovative, interactive methods, technologies, this task can be done. In addition, the creativity of students is very important for language learning.